Penerapan Model Problem Based Learning Dalam Meningkatkan Hasil Belajar PAI di Kelas XI SMKN 1 Padang - Fikri, Muhammad (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to investigate the effectiveness of the Problem Based Learning (PBL) model in improving student learning outcomes in Islamic Religious Education (PAI). The research was conducted in two cycles. In the first cycle, the implementation of PBL showed good results despite some challenges affecting student engagement. In the second cycle, improvements were made by providing more intensive guidance and adjusting the learning plan, leading to a significant increase in student learning outcomes. The results of the study indicate that in the second cycle, most students achieved the Minimum Mastery Criteria (KKTP) with an average score of 80.92. Overall, the application of the PBL model in PAI lessons effectively improves student learning outcomes by enhancing engagement, group cooperation, and understanding of the material